Aksjologiczne podstawy współczesnej edukacji = Axiological base of contemporary education - Gnitecki, Janusz (1945-2008) (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The work shows the given and set values of a human sense of life. It causes that a man is forced to explore and create them ar the same time. Education is a symbolic communication, which is expressed in the langueage that enables a discemment, understanding, acceptation and respects of values wchich gives a human sense of life. A search for axiologic base of education faces the contemporary theory and practice of education with some difficult and responsible tasks. A human development depends on the solutions of the tasks.
Keywords: aksjologia; edukacja